Pengaruh Penggunaan Model Pembelajaran Inside Outside Cricle (IOC) Terhadap Hasil Belajar Keterampilan Berbicara Siswa Pada Mata Pelajaran Bahasa Indonesia - Elisah Elisah; Andi Besse Marda; Muh. Fihris Khalik; Abrina Maulidnawati; Rahma Ashari Hamzah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims (1) to improve the results of speaking skills in class VII E students of UPTD SMPN 14 Tanralili, (2) to determine the learning outcomes of speaking skills in Indonesian language subjects in class VII E students of UPTD SMPN 14 Tanralili (3) To determine the effect of the learning model Inside Outside Cricle ( IOC ) on speaking skills of class VII E UPTD SMPN 14 Tanralili students . The data collection techniques of this research are (1) tests which include pretest, treatment, and posttest, and (2) documentation. The data analysis technique in this study used the t-test. The results of this study indicate that the pretest is categorized as very low, obtained 10 students who have completed learning speaking skills 31.25% who get a score of 70 and above (meet the KKM) and 22 students who have not completed 68.75% who get score of 70 and below (does not meet the KKM). Meanwhile, after the application of the Inside Outside Cricle (IOC) learning model, the results of the final test (posttest) in the high category were obtained, obtained 26 students who completed poetry learning, namely 81.25% who scored 70 and above and 6 students who did not complete 18. ,75% scored 70 and below.